Analysis of the Partiality in Legal Counseling by Notaries During Extraor-dinary General Meetings of Shareholders Based on the Principle of Justice - Nurjannah, Mira; Gultom, Elisatris; Rukmana, Yenni Yunithawati (IHSA Institute, 2024)
One of the notary's authorities is to provide legal counseling, including in the context of the Extraordinary General Meeting of Shareholders (EGMS). This counseling is very important to ensure the legality of the legal process, especially in the preparation of deeds related to the transfer of shares and other important decisions. However, in practice, there are cases where notaries do not perform their duties independently, which ultimately leads to legal problems. As a country of law, Indonesia guarantees legal certainty and protection for every citizen. However, irregularities by less independent notaries, such as in the case of Notary Hartono in Gianyar Regency, highlight significant risks for the parties involved, including potential losses due to falsification of documents. This study aims to analyze the legal consequences of deeds produced by non-independent notaries. This study seeks to explore how non-compliance by notaries with this principle affects the validity of the deeds they produce. The method used in this study is a normative juridical approach that utilizes secondary data, with analysis carried out on relevant laws and regulations, documents, and literature related to the authority of notaries and the principle of justice. This research is descriptive-analytical, providing an overview of the consequences arising from the lack of independence in the duties of notaries, followed by analysis. The results of the study show that the lack of independence of notaries in providing legal counseling can cause legally defective deeds and potentially void them, resulting in losses for the affected parties. The case of Notary Hartono serves as a concrete example where violations of notary independence lead to forgery of deeds and significant legal repercussions. The principle of justice is not upheld if the notary does not act independently in carrying out his duties